Identification of Susceptibility Genes for Fusarium oxysporum in Cucumber via Comparative Proteomic Analysis - Jun Xu (MDPI AG, 2021)
Fusarium wilt (FW) in cucumber (Cucumis sativus L.), caused by Fusarium oxysporum f. sp. cucumerinum (Foc), poses a major threat to cucumber growth and productivity. However, lack of available natural resistance resources for FW restricts the breeding of resistant cultivars via conventional approaches. Susceptibility (S) genes in susceptible host plants facilitate infection by the pathogen and contribute to susceptibility. Loss of function of these S genes might provide broad-spectrum and durable disease resistance. Here, we screened S genes via comparative proteomic analysis between cucumber cultivars Rijiecheng and Superina, which exhibited resistance and high -susceptibility to FW, respectively. We identified 210 and 243 differentially regulated proteins (DRPs) in the Rijiecheng and Superina, respectively, and further found that 32 DRPs were predominantly expressed in Superina and significantly up-regulated after Foc inoculation. Expression verification found that TMEM115 (CsaV3_5G025750), encoding a transmembrane protein, TET8 (CsaV3_2G007840), encoding function as a tetraspanin, TPS10 (CsaV3_2G017980) encoding a terpene synthase, and MGT2 (CsaV3_7G006660), encoding a glycosyltransferase, were significantly induced in both cultivars after Foc infection but were induced to a higher expression level in Superina. These candidate genes might act as negative regulators of FW resistance in cucumber and provide effective FW-susceptibility gene resources for improving cucumber FW resistance through breeding programs.